Tradisi Omed-omedan dalam Perspektif Industri Budaya - I Nyoman Jayanegara (Badan Riset dan Inovasi Daerah Provinsi Bali, 2019)
The Omed-omedan tradition is one of the unique traditions in the city of Denpasar, precisely in Banjar Kaja, Kelurahan Sesetan. The Omed-omedan tradition is a mythology accepted as a cultural heritage of the Banjar Kaja community, Sesetan, has been passed down from the older generation to the present. That's why this tradition is said to be unique and rare as cannot be found elsewhere. The Omed-omedan tradition was originally a tradition that was carried out spontaneously by the Banjar Kaja community, but in its development it has transformed into a cultural festival which certainly has a fairly high selling value. The transformation of a tradition which was initially carried out spontaneously by the community into a festival showed that the cultural industry with its capitalist ideology was able to influence most people to agree that the implementation of this tradition was packaged into a festival. The Banjar Kaja Sesetan community feels that they need a new model in the implementation of this tradition so that it has more selling value and is better known than before. The Banjar Kaja community, Sesetean, has unconsciously been hegemony by capitalist ideology so that it has unconsciously agreed to transform the tradition from spontaneity into a festival. By reason of the progress of the era and tourism, this tradition is considered to have high economic value so that it should be used as a cultural festival. The cultural industry does not eliminate the sacred value of this tradition, but by turning into a festival with various packages that satisfy the people present, resulting in the loss of the authenticity of the tradition, there has been an unconscious uniformity in the implementation of this tradition.